2020
DOI: 10.3389/fmicb.2020.00546
|View full text |Cite
|
Sign up to set email alerts
|

Iron Limitation in Klebsiella pneumoniae Defines New Roles for Lon Protease in Homeostasis and Degradation by Quantitative Proteomics

Abstract: Nutrient adaptation is key in limiting environments for the promotion of microbial growth and survival. In microbial systems, iron is an essential component for many cellular processes, and bioavailability varies greatly among different conditions. In the bacterium, Klebsiella pneumoniae, the impact of iron limitation is known to alter transcriptional expression of iron-acquisition pathways and influence secretion of ironbinding siderophores, however, a comprehensive view of iron limitation at the protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 76 publications
(88 reference statements)
1
22
0
Order By: Relevance
“…Each condition included four biological replicates. Samples were grown until cells reached mid-log phase, upon which, total proteome analysis was performed as previously described [ 9 ]. Briefly, cells were collected, washed twice with phosphate-buffered saline (PBS), and resuspended in cold 100 mM Tris-HCl (pH 8.5).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each condition included four biological replicates. Samples were grown until cells reached mid-log phase, upon which, total proteome analysis was performed as previously described [ 9 ]. Briefly, cells were collected, washed twice with phosphate-buffered saline (PBS), and resuspended in cold 100 mM Tris-HCl (pH 8.5).…”
Section: Methodsmentioning
confidence: 99%
“…For secretome analysis, the culture supernatant was filtered through a 0.22 μM syringe filter and then performed as previously described [ 9 ]. For each sample, 500 μl of filtered supernatant was treated with DTT, IAA, followed by digestion using LysC and trypsin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies investigating the relationship between K. pneumoniae and transition metal availability focused primarily on iron limitation. These studies found an iron-associated impact on bacterial growth, capsule development, and protease secretion [7][8][9] . Moreover, K. pneumoniae produces siderophores, iron-chelating molecules that can acquire free iron from the environment or acquire it from host proteins, to regulate intracellular iron levels during infection [10][11][12] .…”
Section: Introductionmentioning
confidence: 95%